International Conference on ICT for Smart Society 2013
DOI: 10.1109/ictss.2013.6588106
|View full text |Cite
|
Sign up to set email alerts
|

Event detection in social media: A survey

Abstract: The emergence of social media open a lot of research opportunity. Information from social media could be used for many things, such as detecting event, predicting event, and even for early warning system. This paper describe topics related to analyzing social media for detecting four types of event, that is, disaster, traffic, outbreak, and news. Several approaches used to analyze social media data are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Consequently, a number of surveys exist that document the current state of the art. For example, the survey presented by Nurwidyantoro and Winarko [8] summarizes techniques to detect disaster, traffic, outbreak and news events. The survey by Madani et al [9] presents techniques that each address one of the four challenges of health epidemics identification, natural events detection, trending topics detection and sentiment analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a number of surveys exist that document the current state of the art. For example, the survey presented by Nurwidyantoro and Winarko [8] summarizes techniques to detect disaster, traffic, outbreak and news events. The survey by Madani et al [9] presents techniques that each address one of the four challenges of health epidemics identification, natural events detection, trending topics detection and sentiment analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As extensions of our evaluations we plan to include further parameter settings and to research the interdependencies of the parameters. By reviewing the surveys of related work (e.g., Nurwidyantoro and Winarko [20], Madani et al [15], or Farzindar and Khreich [10]), we found several candidates for this venture. On the one hand, techniques such as TwitterMonitor [16] and Twevent [13] are interesting because the techniques they use are closely related to our own techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, Twitter gained significant importance for researchers, especially in the context of event detection techniques applied to social media data streams. The great variety of event detection techniques for Twitter is also reflected in a couple of recently presented surveys [6], [9], [18], [23], [36]. At the same time and with the same variety, methods to evaluate the results of event detection techniques for Twitter appeared.…”
Section: Issues Of Reproducibiltymentioning
confidence: 99%